Effect of Chair-Based Active and Passive Exercise on Activities of Daily Living Independence Among Older Adults: A One-Group Pretes-Posttest Study - Latifah Windi Astuti; Arif Fadli Muchlis; Liza; Iit Selviani (Jurnal Master Penjas & Olahraga, 2026)
Ageing is accompanied by declines in muscle strength, balance, and joint flexibility that may reduce independence in activities of daily living (ADL). This one-group pretest-posttest study evaluated a four-week chair-based active and passive exercise programme among 15 older adults selected purposively at the Sabai Nan Aluih Sicincin Social Nursing Home. The intervention was delivered three times weekly for 12 sessions, and ADL independence was assessed with the Katz Index. The mean score increased from 3.13 (95% CI 2.78-3.48) to 4.00 (95% CI 3.58-4.42). The Wilcoxon signed-rank test showed a significant pre-post difference (Z = -3.36, p < .001) with a large effect size (r = .867). The programme was associated with improved functional independence and may be incorporated into supervised activity routines in residential care, while controlled studies are needed to confirm causality.